Bibliographic Analysis of Pain Research Published in Indexed Journals in Pakistan. A 10-Year Survey - Ausaf Ahmed Khan; Gauhar Afshan (Annals of Abbasi Shaheed Hospital and Karachi Medical & Dental College, 2022)
Objective: The aim of this study was to identify bibliographic characteristics of pain-related articles published from 2011 to 2020 in indexed journals of Pakistan. Methods: This retrospective study was conducted after approval from the departmental research committee at the Department of Anaesthesiology from July 2022 to August 2022. A literature search was carried out to identify pain-related articles published between January 2011 and December 2020 in Pakistani journals indexed in the National Library of Medicine (NLM) Catalog. For information on authors and articles, both authors reviewed each journal's website and its archives. Articles on molecular and animal research were excluded. Data collected by the two authors were compared to check for accuracy, missing data, or other discrepancies. Data was recorded on predesigned Excel ? worksheets, and SPSS ? version 19 was used for data analysis and reporting. Results: Our study revealed a steadily rising number of research articles published. The number of publications increased from 7 articles in 2011 to 28 in 2020. The extracted articles represented publications originating from 9 different countries, and out of 138 publications, 109 (78.99%) were identified as original articles. The significant contribution to "pain" research is from the discipline of Anaesthesia, 24.64%. However, research output on "Chronic Pain" was only 12.73% from the discipline of Anaesthesia. Conclusion: This study demonstrated a multispecialty contribution to the area of pain research, with anesthesiology providing a considerable contribution, although the contribution from anaesthesia in chronic pain is fairly modest.